Youth and the politics of generational memories: The Soweto uprising in South Africa - Sandrine Gukelberger (Ateliers d'Anthropologie)
This article deals with the individual histories of local politicians and activists in urban South Africa (Cape Town), in which the past is situated in relation to the present. It looks at those who were youths during apartheid and who are now involved in urban politics. This article sheds light on how members of the historical generation of Soweto have produced knowledge, and how these textured experiences have steered them towards certain political commitments. Through their stories, it can be seen how the Soweto generation is commonly taken to symbolise the outbreak of the youth rebellion in 1976. Taking the narrative of the Soweto generation from apartheid to democracy as a point of departure, this article suggests that a historicising, gendered perspective is vital to understanding the continuities and discontinuities in the speeches, representations, and rationales for action in youth activism and local politics in contemporary South Africa. The diverse ways of experiencing and remembering Soweto not only structured pathways for specific actors, but became part of the symbolic repertoire of politics as such in South Africa.